Proyecto de factibilidad para la implementación de una empresa productora de marcos para espejos en hierro forjado para la ciudad de Loja, provincia de Loja - Carrión Unda, Daysi Maribel (2017)
The aim of this is to determine the feasibility of implementing a company producing frames for mirrors in wrought iron and marketing in the city of Loja, for which the application of different methods and techniques requires, regarding the methods was used, the Deductive; Inductive and Analytical Synthetic. The use of them allowed to meet the objectives, and follow in the footsteps of understanding and demonstration of the same application. For the above reasons, the market research was conducted first by a survey f a sample of 397 families (demand) and 315 companies offering mirror frames (supply), has determined the potential demand for 52.827, the Real Demand 69.732 frames for mirrors, Effective Demand of 48.812 frames for mirrors in wrought iron, the offer of 29.106 frames for mirrors wrought iron and unsatisfied demand of 19.706 frames for mirrors is determined wrought iron, which determines that the project can be run from the market perspective. Within the technical study, the installed capacity at 20.080 frames for mirrors in wrought iron, whose capacity utilization will be 16.064 frames for mirrors wrought iron, is determined also determined that the location of the company will be in the city of Loja, in the Balsas streets and Sta. Rosa. The production process requires the use of suitable equipment, which will guarantee for quality service and moderate prices. Likewise and administrative study determined as a Limited Liability Company, with functional organizational structure considering both legislative hierarchical levels, Executive, Consultant Level Support Assistant, Level Operational Level and manuals functions performed. In the financial study, it is mentioned that the project reaches an investment of $ 19.918,05 and will be financed with a contribution or partners 54.81% of the total investment and a loan that will keep the project with the bank Development will constitute the 45.19%. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 84.467,11 for this project IRR is 96.91; the time required to recover the original investment would be 1 year and nine days, the sensitivity values are less than one, therefore do not affect the project changes in costs and increased revenues decreased in 30.55 and 20,36% respectively, is the project is not sensitive to these changes. Finally the most significant conclusions and recommendations of the project are proposed.